Kajian pendahuluan pendugaan cepat densitas Spirulina sp dengan turbiditimeter untuk studi ekotoksikologi di era revolusi industri 4.0 (Preliminary study of quick assessment of Spirulina sp density using turbiditymeter for ecotoxicological studies in 4.0 industrial revolution era) - Khusnul Yaqin; Nur Fadhilah Rahim; Liestiaty Fachruddin; Rahmadi Tambaru (Jurnal Pengelolaan Perairan, 2019)
Estimating the number of phytoplankton is something important in the field of aquatic science, including the field of aquatic ecotoxicology. Turbiditimeter is a device that can determine the level of turbidity of the water both caused by non-organic and organic matter, such as phytoplankton. Preliminary research has been conducted to estimate the number of phytoplankton, Spirulina, using turbiditymeter. The results showed that the correlation between the number of Spirulina which was directly estimated using the haemocytometer and the turbidity level detected by the turbiditimeter was statistically very strong and significant statistically (R = 0.9762 and S = 0.012). The linear equations of the correlation can be used to estimate the number of Spirulina with an error of 4.17-20.99% indirectly.  The conclusion of this study is that turbiditimeter can be used to predict the number of phytoplankton indirectly.Keywords : Quick assesment, ecotoxicology, Spirulina sp, turbidimetry, revolution, industry 4.0